The P-SSP7 cyanophage has a linear genome with direct terminal repeats. - Gazalah Sabehi; Debbie Lindell (PLoS ONE)
P-SSP7 is a T7-like phage that infects the cyanobacterium Prochlorococcus MED4. MED4 is a member of the high-light-adapted Prochlorococcus ecotypes that are abundant in the surface oceans and contribute significantly to primary production. P-SSP7 has become a model system for the investigation of T7-like phages that infect Prochlorococcus. It was classified as T7-like based on genome content and organization. However, because its genome assembled as a circular molecule, it was thought to be circularly permuted and to lack the direct terminal repeats found in other T7-like phages. Here we sequenced the ends of the P-SSP7 genome and found that the genome map is linear and contains a 206 bp repeat at both genome ends. Furthermore, we found that a 728 bp region of the genome originally placed downstream of the last ORF is actually located upstream of the first ORF on the genome map. These findings suggest that P-SSP7 is likely to use the direct terminal repeats for genome replication and packaging in a similar manner to other T7-like phages. Moreover, these results highlight the importance of experimentally verifying the ends of phage genomes, and will facilitate the use of P-SSP7 as a model for the correct assembly and end determination of the many T7-like phages isolated from the marine environment that are currently being sequenced.